Study of socio-demographic factors in cases of pregnancy induced hypertension and its associated risk factors in a tertiary care hospital - Bairwa, Radheshyam; Mandve, Shikha; Sharma, Savitri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The aim of the study was to study the socio-demographic factors in cases of pregnancy induced hypertension and its associated risk factors in a tertiary care hospital. Methods: The present retrospective study was conducted in the obstetrics and gynecology department of Shrimati Heera Kunwar Baa Memorial Hospital, Jhalawar, Rajasthan from December 2018 to November 2019. A total of 80 cases of pregnant women with PIH were studied. The socio-demographic data like age, parity, gestational age of presentation, mode of delivery, maternal and perinatal complications were noted from the hospital records and studied. Results: The incidence of PIH was found to be 8.16% in pregnant women attending the SHKBM Hospital. Majority of the study subjects were rural dweller (70%). A higher incidence of PIH was found among illiterate women (51.25%). 53.75% cases were in the age group of 25-30 years and 25% were in the age group of 19-24 years. In the present study, incidence of PIH was found to be highest among primigravidas (67.50%) as compared to multigravidas (32.5%). Most cases were delivered by caesarean section (73.75%) and 26.25% were delivered vaginally. Out of 80 cases, 16.25% of cases were complicated by eclampsia, Severe PIH in 12.5%, abruptio placentae in 2.5% and HELLP Syndrome in 1.25% cases. Conclusions: PIH is a very common complication encountered in pregnancy associated with adverse maternal and fetal outcome. The risk is higher among young primigravidas and in rural population. Better health care facilities and awareness among the pregnant women will help in reducing the incidence of PIH and its associated complications.